About Joint Program of Ministry of Health and National Academy of Medical Sciences of Ukraine «Medical treatment at traumatic brain injury» - Pedachenko, Eugene; Huk, Andriy (Ukrainian Neurosurgical Journal, 2014)
No abstract.